2017
DOI: 10.1103/physreve.95.013203
|View full text |Cite
|
Sign up to set email alerts
|

Mixing with applications to inertial-confinement-fusion implosions

Abstract: Approximate 1D as well as 2D and 3D simulations are playing an important supporting role in the design and analysis of future experiments at NIF. This paper is mainly concerned with 1D simulations, used extensively in design and optimization. We couple a 1D buoyancy-drag mix model for the mixing zone edges with a 1D Inertial Confinement Fusion (ICF) simulation code. This analysis predicts that National Ignition Campaign designs are located close to a performance cliff, so that modeling errors, design features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Recently, different simulations by [1] showed that the growth of the viscosity coefficient, as the deuterium-tritium plasma heats up to the kinetic regime [2], dissipates the turbulent kinetic energy. It also inhibits the growth of Rayleigh-Taylor or Kelvin-Helmholtz instabilities [3], impacts the mean radial flow [4], and possibly influences the turbulent mixing in the central hot spot, where fusion processes set in [5]. The suddenness of this effect can substantially participate in a local temperature increase by rapidly converting the kinetic energy into an internal one [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different simulations by [1] showed that the growth of the viscosity coefficient, as the deuterium-tritium plasma heats up to the kinetic regime [2], dissipates the turbulent kinetic energy. It also inhibits the growth of Rayleigh-Taylor or Kelvin-Helmholtz instabilities [3], impacts the mean radial flow [4], and possibly influences the turbulent mixing in the central hot spot, where fusion processes set in [5]. The suddenness of this effect can substantially participate in a local temperature increase by rapidly converting the kinetic energy into an internal one [6].…”
Section: Introductionmentioning
confidence: 99%
“…Combined instabilities such as the BDI have been shown to be particularly troublesome for ICF; making their elucidation a crucial step for the viability of this technology [12][13][14][15][16][17]. Laser drive asymmetry and fabrication irregularities create perturbations that grow due to combined instability during the initial implosion stage and later on when compressed hot fuel decelerates the colder imploding fuel [15][16][17][18].…”
Section: A Problem Outline and Motivationmentioning
confidence: 99%
“…Furthermore, it has been found that the ICF operating regime is located on a performance cliff, meaning small deviations in model design could have a large impact on performance [12]. This predicament provides impetus to rigorously test the simulations, and their models, used in ICF design as much as possible.…”
Section: A Problem Outline and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19,20 ] Therefore, the negative effects of impurities in fuel ignition have always been considered and studied by many researchers. [ 21,22 ] Mixing of the fuel with inactive materials can occur during the compression and hot‐spot formation stages. A cryogenic FI target is designed as a hollow multilayer shell (filled with dilute DT gas) and a hollow cone.…”
Section: Introductionmentioning
confidence: 99%